2007
DOI: 10.1002/adsc.200700079
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of N‐Heterocyclic Carbene Substituted Phosphine and Phosphite Rhodium Complexes and their Catalytic Properties in Hydrogenation Reactions

Abstract: Mixed N-heterocyclic carbene-substituted phosphine and phosphite complexes of rhodium were prepared, starting from [RhA C H T U N G T R E N N U N G (COE) 2 Cl] 2 (COE = cyclooctene) by addition of free N-heterocyclic carbenes (NHC) and PR 3 . All new complexes were characterized by spectroscopy. In addition, the structures of trans-chloro(1,3-dicyclohexylimidazol-2-ylidene)-bis(triphenylphosphite)rhodium(I) (5), chloro-trans-bis(1,3-dicyclohexylimidazol-2-ylidene) (triphenylphosphine)rhodium(I) (6), and chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 108 publications
3
28
0
Order By: Relevance
“…30-40 % after 5 h). Our findings generally parallel closely more detailed studies reported by Herrmann et al, [9] who tested RhCl(COD)(NHC) and [Rh(COD)(NHC) 2 ] + in toluene for catalytic hydrogenation of cyclohexene and 1-octene; in these systems, addition of PPh 3 was needed to generate effective catalysts. Nolan's group has reported low activity for RhCl(IMes)(PPh 3 ) 2 for hydrogenation of cyclohexene, [20] but this study was carried out in CH 2 Cl 2 not generally a favoured solvent because hydrogen transfer to the solvent can occur with liberation of HCl.…”
Section: Catalytic Hydrogenationssupporting
confidence: 92%
See 4 more Smart Citations
“…30-40 % after 5 h). Our findings generally parallel closely more detailed studies reported by Herrmann et al, [9] who tested RhCl(COD)(NHC) and [Rh(COD)(NHC) 2 ] + in toluene for catalytic hydrogenation of cyclohexene and 1-octene; in these systems, addition of PPh 3 was needed to generate effective catalysts. Nolan's group has reported low activity for RhCl(IMes)(PPh 3 ) 2 for hydrogenation of cyclohexene, [20] but this study was carried out in CH 2 Cl 2 not generally a favoured solvent because hydrogen transfer to the solvent can occur with liberation of HCl.…”
Section: Catalytic Hydrogenationssupporting
confidence: 92%
“…[18] In our case, the Rh-H hydrides were not located even though residual electron density around the Rh was evident. The two IPr ligands are mutually trans [177.1 (2) [2,4,5,9,18,28] ). Crudden and co-workers have synthesized complex 5 from the nitrogen complex trans-RhCl(N 2 )(IPr) 2 , and have also obtained a crystal structure for 5 which co-crystallized with the Rh II complex RhCl 2 (IPr) 2 ; their determined crystallographic geometrical parameters for a non-solvated crystal of 5 are close to our values, and they were able also to locate the hydrides (Rh-H = 1.45 Å).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations